2010
DOI: 10.1007/s00134-010-1954-x
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion-related acute lung injury in ICU patients admitted with gastrointestinal bleeding

Abstract: Purpose Transfusion of blood components is common in patients admitted to the intensive care unit (ICU) for gastrointestinal (GI) bleeding, yet the incidence and risk factors for development of transfusion-related acute lung injury (TRALI) in these patients are unknown. Methods Patients admitted to a medical ICU for GI bleeding (n = 225) were analyzed for patient-and transfusion-specific risk factors for development of TRALI. Results In transfused patients (n = 150), the incidence of TRALI was 15% [95% con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
72
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 34 publications
2
72
0
Order By: Relevance
“…Furthermore we notified a significant reduction in the development of ARDS, which may be causally linked to a reduced transfusion of fresh frozen plasma in these patients. This is an interesting and at least potentially essential observation for that the transfusion of FFP has also been shown to be responsible for the development of TRALI [33][34][35]. More and above, the reduction of FFP administration itself may also be responsible for the reduction of pRBC transfusion as observed in our present study and has also been shown in a prospective cohort study by Innerhofer and coworkers [36].…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore we notified a significant reduction in the development of ARDS, which may be causally linked to a reduced transfusion of fresh frozen plasma in these patients. This is an interesting and at least potentially essential observation for that the transfusion of FFP has also been shown to be responsible for the development of TRALI [33][34][35]. More and above, the reduction of FFP administration itself may also be responsible for the reduction of pRBC transfusion as observed in our present study and has also been shown in a prospective cohort study by Innerhofer and coworkers [36].…”
Section: Discussionsupporting
confidence: 87%
“…[1][2][3][4] TRALI is defined as the acute onset of hypoxia and bilateral pulmonary infiltrates, in temporal relation to a blood transfusion. 1,5 Although the absence of specific disease markers and diagnostic tests has resulted in a large variation in estimations of incidence, 1,[6][7][8][9][10][11][12][13][14] TRALI is generally considered to be a rare event. However, TRALI is underdiagnosed and under-reported.…”
Section: Introductionmentioning
confidence: 99%
“…Only one (21) of seven contemporary studies examining patientrelated TRALI risk factors (4,(6)(7)(8)(21)(22)(23) details how the investigators determined ARDS onset time. Other studies found that expert investigators frequently do not agree on the radiographic definition of ARDS (24,25), which further adds to the concern of unreliability of the TRALI definition raised by our study.…”
Section: Original Research Discussionmentioning
confidence: 99%